Characterization of Novel Plant Symbiosis Mutants Using a New Multiple Gene-Expression Reporter Sinorhizobium meliloti Strain - Lang, Claus; Smith, Lucinda S.; Haney, Cara H.; Long, Sharon R. (Frontiers in Plant Science, 2018)
The formation of nitrogen fixing root nodules by Medicago truncatula and Sinorhizobium meliloti requires communication between both organisms and coordinated differentiation of plant and bacterial cells. After an initial signal exchange, the bacteria invade the tissue of the growing nodule via plant-derived tubular structures, called infection threads. The bacteria are released from the infection threads into invasion-competent plant cells, where they differentiate into nitrogen-fixing bacteroids. Both organisms undergo dramatic transcriptional, metabolic and morphological changes during nodule development. To identify plant processes that are essential for the formation of nitrogen fixing nodules after nodule development has been initiated, large scale mutageneses have been conducted to discover underlying plant symbiosis genes. Such screens yield numerous uncharacterized plant lines with nitrogen fixation deficient nodules. In this study we report construction of a S. meliloti strain carrying four distinct reporter constructs to reveal stages of root nodule development. The strain contains a constitutively expressed lacZ reporter construct; a PexoY-mTFP fusion that is expressed in infection threads but not in differentiated bacteroids; a PbacA-mcherry construct that is expressed in infection threads and during bacteroid differentiation; and a PnifH-uidA construct that is expressed during nitrogen fixation. We used this strain together with fluorescence microscopy to study nodule development over time in wild type nodules and to characterize eight plant mutants from a fast neutron bombardment screen. Based on the signal intensity and the localization patterns of the reporter genes, we grouped mutants with similar phenotypes and placed them in a developmental context.